193k views
5 votes
Select the correct answer from each drop down menu

Select the correct answer from each drop down menu-example-1
User Robotbugs
by
4.4k points

1 Answer

3 votes

Answer:


(f*g)(x) = 4x^5-16x^3+x^2-4

Explanation:

We are given the following functions:


f(x) = 0.5x^2-2


g(x) = 8x^3+2

Using both functions we need to find value of (f*g)(x).

(f*g)(x) simply means find product of f(x) and g(x) so we will multiply values of each function as shown below:


(f*g)(x) = (0.5x^2-2)(8x^3+2)


(f*g)(x) = 0.5x^2(8x^3+2)-2(8x^3+2)


(f*g)(x) = 4x^5+1x^2-16x^3-4


(f*g)(x) = 4x^5-16x^3+1x^2-4


( f * g ) ( x ) = 4 x ^ 5 - 1 6 x ^ 3 + x ^ 2 - 4

User Jzheaux
by
4.9k points